2022
DOI: 10.1080/22221751.2022.2059405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of interleukin-6 receptor antagonists (tocilizumab and sarilumab) in patients with COVID-19: a systematic review and meta-analysis

Abstract: This study investigated the efficacy and safety of interleukin-6 (IL-6) receptor antagonists with standard care treatment in patients with coronavirus disease 2019 (COVID-19). The randomized controlled trials were identified through systematic searches of electronic databases through February 10, 2022. In total, 17 trials comprising 8,614 patients were included. Compared with exclusive standard care or placebo, IL-6 receptor antagonists with standard of care treatment were associated with a significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
0
19
0
5
Order By: Relevance
“…We considered also testing the efficacy of IL-1 and IL-6 neutralization. Recent findings have supported the use of anti-IL-1/IL-1R and anti-IL-6 mAbs in patients with severe COVID-19 (45)(46)(47), and these treatments have been approved by the US Food and Drug Administration for emergency usage in hospitalized patients with COVID-19 with systemic inflammation. Testing the potential of neutralizing these cytokine pathways in combination with GM-CSF administration for prevention of lethality during SARS-CoV-2/S.…”
Section: Discussionmentioning
confidence: 92%
“…We considered also testing the efficacy of IL-1 and IL-6 neutralization. Recent findings have supported the use of anti-IL-1/IL-1R and anti-IL-6 mAbs in patients with severe COVID-19 (45)(46)(47), and these treatments have been approved by the US Food and Drug Administration for emergency usage in hospitalized patients with COVID-19 with systemic inflammation. Testing the potential of neutralizing these cytokine pathways in combination with GM-CSF administration for prevention of lethality during SARS-CoV-2/S.…”
Section: Discussionmentioning
confidence: 92%
“…Un bénéfice des inhibiteurs du récepteur de l’IL-6 sur la mortalité brute a été observé dans de nombreux travaux [ [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] ]. Ce bénéfice est présent dans certaines méta-analyses seulement lorsque le modèle statistique utilisé est à effet fixe.…”
Section: Essais Cliniquesunclassified
“…146 Furthermore, research by Yu et al found that sarilumab was not significantly associated with a reduced risk of invasive mechanical ventilation (RR 1.15; 95%CI, 0.38-3.51), whereas tocilizumab reduced the risk by 21% (RR 0.79; 95%CI, 0.71-0.88). 147 The differences between the two may be due to the limited number of studies which have evaluated the effects of sarilumab, compared with tocilizumab, or the different mechanisms of action. Sarilumab blocks IL-6 and IL-6 receptors, but tocilizumab is only an IL-6 receptor antagonist.…”
Section: Publication Biasmentioning
confidence: 99%